(untitled) (Research, Society and Development, 2021)
Composite resin is one of the most used dental materials by professionals, aiming at the search for aesthetic and functional restoration of the teeth. In this context, this study aimed to verify the factors that influence the longevity of direct restorations. An integrative literature review was performed, in which the bibliographic survey was performed through consultation in databases of relevance to the production of health knowledge: PubMed / Medline and SCIELO, in Portuguese and English, in full, between January 2009 and January 2019, totaling 20 articles. According to the researched articles, fractures are reported in almost 100% of the studies as a reason for failure of composite resin restorations, followed by secondary caries and lack of hygiene by the patient. Regarding the main factors for resin longevity, studies show that the choice of material, the size of the cavity, the use of barrier material to prevent oral pathogens (absolute isolation), the need for proper polishing and finishing. and above all, the implementation of a regular prophylaxis program. Therefore, it should be borne in mind that efforts for diagnosis, planning, treatment indication, correct procedure execution, observation of occlusal aspects, biofilm control and follow-up are essential to obtain results aimed at direct restoration longevity.